Inclusive Education in Indonesian Madrasah Ibtidaiyah: A Qualitative Meta-Synthesis of Dual Curriculum Challenges and Pedagogical Adaptations - Kim, Daemin; Juju Masunah; Rita Milyartini (UIN Sunan Kalijaga Yogyakarta, 2026)
This systematic literature review aims to evaluate the pedagogical strategies, theological foundations, and structural challenges of inclusive education in Indonesia’s Madrasah Ibtidaiyah (Islamic primary schools). Utilizing a PRISMA-guided screening protocol and data extraction form as the primary research instrument, 29 empirical studies and policy documents published between 2016 and 2026 were purposively selected from major academic databases. Data analysis was conducted through qualitative thematic meta-synthesis to systematically code and categorize the findings. The analysis reveals that while Islamic values of Rahmah (compassion) and Adl (justice) provide a strong theological imperative for inclusion, implementation is frequently obstructed by resource scarcity and policy dualism. Key pedagogical findings indicate a reliance on peer-mediated interventions, the adaptation of traditional Quranic methods like Takrir for neurodivergent students, and the crucial role of shadow teachers (Guru Pembimbing Khusus). Ultimately, achieving sustainable inclusion requires a paradigmatic shift from charitable integration to rights-based inclusion, necessitating the formal institutionalization of Fikih Difabel (disability jurisprudence) and Universal Design for Learning (UDL) frameworks.